The Dutch Labour Market Early on in the COVID-19 Outbreak: Regional Coronavirus Hotspots and the National Lockdown - Wolter Hassink; Guyonne Kalb; Jordy Meekes (Institute of Labor Economics (IZA), 2020)
We explore the impact of COVID-19 hotspots and regional lockdowns on the Dutch labour market. Using weekly administrative panel microdata for 50 per cent of Dutch employees until the end of March 2020, we study whether individual labour market outcomes, as measured by employment, working hours and hourly wages, were more strongly affected in provinces where COVID-19 confirmed cases, hospitalizations and mortality were relatively high. We do not observe a region-specific impact of COVID-19 on labour market outcomes. The results suggest individual characteristics are more important, including the employee's age, type of contract and type of job. The evidence suggests that the decline of the labour market was all due to the impacts from the government-enforced lockdown and higher virus case numbers did not reinforce this decline. This suggests that preventive health measures should be at the regional level, isolating hotspots from low-risk areas.
Keywords: I15; I18; J20; J30; J64; 330; COVID-19; coronavirus hotspots; lockdown; employment; working hours; wages